Thermodynamic behavior of Na-majorite and knorringite-majorite garnet systems - Gaurav S.; Shankar S.; Raghav Anamika; Kumari Pratibha; Singh Manish (Russian Journal of Earth Sciences)
The behavior of thermal parameters pressure (P) and thermoelastic parameters i.e. Isothermal bulk modulus (K_T), its pressure derivative (K'T) and Thermal expansivity (α) has been analyzed for Na-majorite and knorringite-majorite systems at different compressions down to a maximum value of 0.3 for temperature ranges from 300 K to 1500 K. The pressure dependent compressibility of these garnets have been studied. The comprehensive study of thermodynamic and thermoelastic behavior at different isotherms and isobars respectively has been achieved by employing both Vinet equation of state and Anderson-Isaak equation. The study of thermal expansivity (α) using Anderson-Isaak and Stacy-Davis approach shows a similar trend of MgO system. Based on the validation of Kumar's approach, the lattice parameter of garnet system is computed using Kumar and modified Kumar's approach at high temperature and is found to be very less deviated from the value of lattice parameter at room temperature.